Analyzing Information Systems to Manage Hospitals Through Application Using the HOT-FIT (Human Organisation Technology-FIT) Concept (Universitas Muhammadiyah Yogyakarta, 2025)
The Hospital Management Information System (SIMRS) is a technology-based solution that facilitates seamless interaction and coordination among hospital departments. It enhances administrative workflows, reporting accuracy, and overall operational efficiency, while maintaining the integrity and reliability of the data collected. A quantitative research methodology was employed, with data collected through a meticulously designed questionnaire that incorporated closed-ended questions and a Likert scale. The data from 98 respondents were examined using PLS-SEM through SmartPLS 3 software. The analysis revealed several strategies to enhance the performance of SIMRS. User satisfaction and the state of the facilities made up 60.6% of the perceived benefits. System quality, information quality, service quality, and organizational structure collectively had a 61.5% effect on user satisfaction. System quality and user involvement had a 55% effect on the development of the system. System quality, user satisfaction, and leadership support were found to contribute 61.5% to user engagement. Hospital administrators are advised to adopt the HOT-FIT model as a strategic framework for ongoing performance evaluations and assessments. By consistently monitoring system quality, user satisfaction, and organizational backing, they can detect issues early and foster continuous improvements in digital healthcare services.